Miss Tizzy - Gray, Libba Moore; Rowland, Jada (New York : Simon & Schuster Books for Young Readers, 1993)
The eccentric Miss Tizzy, a beloved friend to all the children in her neighborhood, needs their help in remaining happy when she is sick in bed.
Keywords: Individuality -- Fiction; Sick -- Fiction; African Americans -- Fiction